Investigation of Steady State Two-Phase Short Circuit Modes Of Phase-Shifting Autotransformer with Hexagon Scheme and with Adjusting Autotransformer - Bosneaga V.; Suslov V. (Problems of the Regional Energetics)
The purpose of work is to investigate two - phase short-circuiting modes of new autotransformer FACT’s - type device and is intended for power systems flexible connection. The developed mathematical model contains the main phase-shifting and additional regulating autotransformers. The model allows studying of asymmetrical modes of such schemes, including the un-identical load connection in different phases of phase-shifting transformers. Visual vector diagrams of winding’s voltages, currents and relative magnetic fluxes of magnetic core legs for main and regulating autotransformers for the modes with two-phase short-circuiting with and without ground have been elaborated. It is shown that significant distortions of the polygon shape occurred. It is revealed that in two-phase short - circuiting mode without ground, and the loads identically connected in different phases, the relative magnetic fluxes of the legs of main and regulating autotransformers are asymmetrical, but their sum is zero, and the magnetic flux does not come out into surrounding space. Load currents in this mode contain only direct and reverse sequences components. When the load is un-identically connected in different phases, significant zero-sequence currents occur, and magnetic flux goes out into surrounding space. However, load currents do not contain symmetrical components of zero sequence. A similar analysis of two-phase short circuit modes with ground showed that even with the identical connection of the loads, there is zero sequence both in the magnetic fluxes and in the load currents. Moreover, zero sequence is present when the load is connected differently on the phases.